1962
DOI: 10.1111/j.1939-0025.1962.tb00258.x
|View full text |Cite
|
Sign up to set email alerts
|

The sins of the fathers: Urban decay and social pathology.

Abstract: Clinical study of emotionally disturbed foster children raises disquieting questions as to the adequacy of the care foster children are receiving from understaffed public agencies. Members of the orthopsychiatric professions bear a heavy moral responsibility, precisely because of our scientific knowledge of the needs of children, to provide leadership for community action to correct social and institutional hazards that impair the physical and mental health of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
2

Year Published

1967
1967
1996
1996

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Shah (1972), Schor (1982), Moffat et al (1985), and McIntyre and Keesler (1986) found psychological problems in 35% to 49% of foster children, whereas Eisenberg (1962), Shah (1974b), Kavaler and Swire (1983), and Frank (1980) documented that 30% to 80% of children examined for psychological problems were moderately to severely impaired.…”
Section: Health Status and Utilization Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shah (1972), Schor (1982), Moffat et al (1985), and McIntyre and Keesler (1986) found psychological problems in 35% to 49% of foster children, whereas Eisenberg (1962), Shah (1974b), Kavaler and Swire (1983), and Frank (1980) documented that 30% to 80% of children examined for psychological problems were moderately to severely impaired.…”
Section: Health Status and Utilization Patternsmentioning
confidence: 99%
“…Any ongoing health care they may have had is interrupted. Therefore, although removal from the home and placement in foster care is intended to be a therapeutic intervention, it also may contribute to a child's poor health (Eisenberg, 1962;Fine, 1989;Schor, 1988).…”
mentioning
confidence: 99%
“…Beck (1971) observed that more than 300,000 children are in foster care in this country at any one time and that, of these, 100,000 have no hope of ever returning to ',heir own families. Eisenberg (1962) reported on a number of years' experience in assessing children in foster care referred for psychiatric evaluation. He found that the neglected child in foster care had many more psychological problems than the aver age child placed for less ominous reasons.…”
Section: Antisocial Behaviormentioning
confidence: 99%
“…It is also understood that many children from neglect situations require facilities beyond the ability of loving foster parents to supply (Eisenberg, 1962). Therefore, the institution continues to have a definite role.…”
Section: Placementmentioning
confidence: 99%
“…I n contrast, a great deal of research and theory has been published concerning the influence of family variables oq measures of children's adjustment other than the BPCL. In general, the literature suggests the following conclusions: (a) Children who live with both of their natural parents have fewer problems than those living with only one natural parent or relatives (Gregory, 1965;Tuckman & Regan, 1966) and than those placed with adoptive families (Schechter, Carlson, Simmons, & Work, 1964;Witmer, Hersog, Weinstein, & Sullivan, 1963) or with foster families (Eisenberg, 1962). (b) Ordinal position and number of other children in the family expose youngsters to different experiences.…”
mentioning
confidence: 99%